The impact of green fiscal policy on green technology investment: Evidence from China - Vitenu-Sackey, Prince Asare; Oppong, Stephen; Akpemah Bathuure, Isaac (International Journal of Management Excellence (ISSN: 2292-1648), 2021)
Our objective is to investigate the impact of green fiscal policy on green technology investment in China. We employed some econometric techniques as our strategy for the empirical analysis. We used a quantile regression with the lad method in our long-run estimations. The results suggest that green fiscal policy has a heterogeneous impact on green technology investment total factor productivity considering the kind of proxy and magnitude of the coefficients. However, we observed that environmental tax as a proxy measure of green fiscal policy positively impacts green technology investment total factor productivity while environmental expenditure negatively does. Our findings imply that when green technology investment total factor productivity is on the ascendency, increasing the existing energy consumption structure could decrease green technology investment total factor productivity. In other words, provinces with a higher level of green technology investment total factor productivity should ensure a reduction in their existing energy consumption structure to promote green technology investment. Also, we conclude that green technology investment progress is opposed by increasing research and development, gross domestic product, and existing energy consumption structure through environmental expenditure. To sustain green technology investment progress, environmental taxes be increased substantially to deter polluters by adopting green technologies.